225k views
5 votes
Solve the system (x-1)²+(y-2)²=2² and y=2x+2.

User BeniBela
by
6.0k points

1 Answer

5 votes

Answer:

(x, y) = (-0.6, 0.8) or (1, 4)

Explanation:

Use the second equation to substitute for y in the first.

(x -1)² +((2x +2) -2)² = 4

x -2x +1 + 4x² = 4 . . . . . . . eliminate parentheses

5x² -2x -3 = 0 . . . . . . . . . . subtract 4, collect terms

Now we can rearrange the middle term to ease factoring by grouping.

(5x² -5x) +(3x -3) = 0

5x(x -1) +3(x -1) = 0

(5x +3)(x -1) = 0

The values of x that make these factors zero are ...

x = -3/5, x = 1

The corresponding values of y are ...

y = 2(-3/5)+2 = 4/5 . . . . for x = -3/5

y = 2(1) +2 = 4 . . . . . . . . for x = 1

The solutions are: (x, y) = (-3/5, 4/5) or (1, 4).

___

A graphing calculator verifies these solutions.

Solve the system (x-1)²+(y-2)²=2² and y=2x+2.-example-1
User Jonathan Nielsen
by
6.7k points